UJI FITOKIMIA DAN TOKSISITAS EKSTRAK METANOL BATANG TANAMAN BINTARO (Cerberra manghas L.) TERHADAP BIBIT IKAN NILA (Oreochromis niloticus) - Febry, Muhammad; Usman, Usman (PROSIDING SEMINAR KIMIA, 2024)
Indonesia is a country located along the equator and has a tropical and subtropical climate. This condition supports the growth of various plant species with high diversity. Bintaro, or Cebera manghas, belongs to the Apocynaceae family and is believed to have potential as a vegetable insecticide. The purpose of this study was to determine the secondary metabolite compounds contained in methanol extract of bintaro plant stems and to determine the toxicity level of methanol extract of bintaro plant stems. This research method consists of 3 stages, namely extraction, phytochemical test (color test) and toxicity test. Extraction is done by maceration method using methanol solvent. Phytochemical test was done by color test. Toxicity test was conducted using BSLT method. The results of the toxicity test of methanol extracts of bintaro plant stems have an LC50 value of 100.697 and obtained the results of phytochemical tests of bintaro plant stems containing alkaloid and flavanoid compounds. Based on the LC50 value, it can be concluded that the methanol extract of bintaro plant stems falls into the medium category and contains alkaloid and flavanoid compounds. Keywords: Cerbera Manghas L., Bintaro, Phytochemical Test, Toxicity Test